Key Techniques and Design Methods of Adhesion Control in Rail Transportation - LI Jianghong; HU Yunqing; PENG Huishui; LIU Liangjie (机车电传动)
Focusing on the specific adhesion phenomenon in railway transportation, characteristic and nature-affected factors of wheelrail adhesion were introduced. Functions of adhesion utilizing control system were described, and key techniques of adhesion utilizing were discussed, as well as principle and theory used by adhesion control system, providing reference and guideline for adhesion control system design.